On discounting and voting in a simple growth model - Kirill Borissov; Mikhail Pakhnin; Clemens Puppe (Karlsruher Institut für Technologie (KIT), Institut für Volkswirtschaftslehre (ECON), 2015)
In dynamic resource allocation models, the non-existence of voting equilibria is a generic phenomenon due to the multi-dimensionality of the choice space even with agents heterogeneous only in their discount factors. Nevertheless, at each point of time there may exist a "median voter" whose preferred instantaneous consumption rate is supported by a majority of agents. Based on this observation, we propose an institutional setup ("intertemporal majority voting") in a Ramsey-type growth model with common consumption and heterogeneous agents, and show that it provides a microfoundation of the choice of the optimal consumption stream of the median agent. While the corresponding intertemporal consumption stream is in general not a Condorcet winner among all feasible paths, its induced instantaneous consumption rate receives a majority at each point in time in the proposed intertemporal majority voting procedure. We also provide a characterization of balanced-growth and steady-state voting equilibria in the case in which agents may differ not only in their time preference, but also in their instantaneous utility functions.
urn:nbn:de:swb:90-513113
Keywords: D11; D71; D91; O13; O43; 330; collective choice; common-pool resource; economic growth; heterogeneous agents; median voter theorem